Timing, Kinematics, and Displacement of the Taltal Fault System, Northern Chile: Implications for the Cretaceous Tectonic Evolution of the Andean Margin. Issue 2 (20th February 2020) - Mavor, S. P.; Singleton, J. S.; Gomila, R.; Heuser, G.; Seymour, N. M.; Williams, S. A.; Arancibia, G.; Johnston, S. M.; Kylander‐Clark, A. R. C.; Stockli, D. F.
Abstract: An extensive system of NW striking faults constitutes a major tectonic feature of the Coastal Cordillera in northern Chile, but fundamental questions remain about timing and kinematics of these structures. We present new geologic mapping and geochronology that provide insight into the structural evolution and tectonic significance of the Taltal fault system (TFS). The TFS displaces the Early Cretaceous arc‐parallel Atacama fault system (AFS) with ~10.6 km cumulative offset across a ~15 km wide zone. Brittle fault data demonstrate that the TFS is vertical to steeply NE dipping with an average sinistral slip vector plunging 11° from the NW, compatible with E‐W shortening. Two late Early Cretaceous dikes cut the AFS but are cut by TFS faults, and synkinematic calcite on a TFS strand yielded a U‐Pb calcite date of 114.1 ± 7.0 Ma. These data demonstrate that the AFS was abandoned and deformation (re) initiated on the TFS between ~114–107 Ma, with continued slip after intrusion of the Tropezón (~110 Ma) and Librillo (106–101 Ma) plutonic complexes. Emplacement of a ~146 Ma rhyolite dike along the main Taltal fault and 141 ± 11 Ma calcite mineralization in the fault core suggests that a precursor structure influenced magma emplacement and fluid flow in the Late Jurassic/Early Cretaceous, supporting the hypothesis that the TFS reactivated long‐lived inherited crustal weaknesses. The Early Cretaceous shift from arc‐parallel shear to slip on the TFS and E‐W shortening shortly preceded migration of the magmatic arc and records a change in the Chilean margin subduction dynamics. Key Points: The Taltal fault system became active between 114 and 107 Ma, shortly after the end of brittle deformation on the Atacama fault system Older dates of structurally controlled intrusions and veining suggest that the Taltal fault system reactivated precursor structures The Taltal fault system records a shift from arc‐parallel shear to E‐W shortening and likely a change in early‐Andean subduction dynamics